Diversion of methadone and buprenorphine from opioid substitution treatment : a staff perspective - Johnson, Björn ; 0000-0002-1601-2706; Richert, Torkel (Journal of Psychoactive Drugs, 2014)
Opioid substitution treatment (OST) is still controversial, despite positive results. The issue of diversion to the illicit drug market is a cornerstone in the criticism typically voiced against the treatment. Little research is available concerning how professionals who work in OST view the issue of diversion. In this article, we discuss existing ideas and attitudes toward diversion of methadone and buprenorphine among OST staff in Sweden. The article is based on semi-structured interviews with 25 professionals working in eight OST-programs in southern Sweden. Diversion was seen as a deleterious phenomenon by the interviewees. Three problematic aspects were highlighted: Medical risks in the form of overdose fatalities and the recruitment of new opiate/opioid users; negative consequences for the legitimacy of OST; and moral objections, since diversion means that the patients remain in a criminal environment. However, positive aspects were also highlighted. Illicit methadone or buprenorphine is perceived as safer than heroin. In this way, diversion can fulfill a positive function; for instance, if there is a shortage of access to regular treatment. Patients who share their medication with opioid-dependent friends are seen as less culpable than those who sell to anyone for money.
2024-02-05T14:03:51.275+01:00
Keywords: buprenorphine; diversion; illicit drug use; methadone; opioid substitution treatment; staff perspective; Social Sciences; Samhällsvetenskap